2022
DOI: 10.1177/13591053211072430
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience is an independent correlate of health-related quality of life in middle-aged and older adults with HIV in the Deep South

Abstract: Older people living with HIV (PLWH) are at risk for poorer health-related quality of life (HRQoL). Psychological resilience may protect HRQoL in this population. The sample included 174 predominately African American PLWH (age 40–73). Results indicated associations between resilience, socioeconomic status, cognitive performance, instrumental activities of daily living, personality, and depressive symptoms. HIV factors (e.g. viral load, duration of HIV) were not associated with resilience. Adjusting for confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…Fumaz et al (2015) reported that less than 20% of their sample had low resilience, suggesting limited variability of participants with high and low resilience and ultimately influencing the results. Hopkins et al (2022) noted that the lack of association between resilience and physical QoL is consistent with some prior research that suggest that psychological factors may not always play a significant role in physical health and well-being. Overall, the association between resilience resources and QoL remained consistent across studies from different countries, suggesting that resilience is a universal resource across cultures.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Fumaz et al (2015) reported that less than 20% of their sample had low resilience, suggesting limited variability of participants with high and low resilience and ultimately influencing the results. Hopkins et al (2022) noted that the lack of association between resilience and physical QoL is consistent with some prior research that suggest that psychological factors may not always play a significant role in physical health and well-being. Overall, the association between resilience resources and QoL remained consistent across studies from different countries, suggesting that resilience is a universal resource across cultures.…”
Section: Discussionsupporting
confidence: 86%
“…Hopkins et al (2022) examined the association between trait resilience and QoL among 174 middle-aged and older PWH (mean age 51.30 years, SD = 7.03). In bivariate correlation analysis, resilience was positively associated with better physical ( r = .20, p < .01) and mental ( r = .42, p < .01) HRQoL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience and well-being are concepts that have been documented extensively. To date, most of this literature (Hopkins et al, in press; Ungar, 2019) ascribes these concepts as individual attributes that help people overcome health challenges to achieve an optimal level of health. The narrow focus of these concepts limits the ability of individuals and societies to achieve health.…”
mentioning
confidence: 99%